The latitudinal gradient in rates of evolution for bird beaks, a species interaction trait. (24th February 2022) - Freeman, Benjamin G.; Weeks, Thomas; Schluter, Dolph; Tobias, Joseph A.
Abstract: Where is evolution fastest? The biotic interactions hypothesis proposes that greater species richness creates more ecological opportunity, driving faster evolution at low latitudes, whereas the 'empty niches' hypothesis proposes that ecological opportunity is greater where diversity is low, spurring faster evolution at high latitudes. We tested these contrasting predictions by analysing rates of beak evolution for a global dataset of 1141 avian sister species. Rates of beak size evolution are similar across latitudes, with some evidence that beak shape evolves faster in the temperate zone, consistent with the empty niches hypothesis. The empty niches hypothesis is further supported by a meta‐analysis showing that rates of trait evolution and recent speciation are generally faster in the temperate zone, whereas rates of molecular evolution are slightly faster in the tropics. Our results suggest that drivers of evolutionary diversification are either similar across latitudes or more potent in the temperate zone, thus calling into question multiple hypotheses that invoke faster tropical evolution to explain the latitudinal diversity gradient. Abstract : Bird beaks evolve faster in the temperate zone than the tropics. This case example illustrates a general trend: rates of trait evolution and speciation tend to be faster in the temperate zone than the tropics.